2014
DOI: 10.1159/000361015
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Bronchoscopy as a Useful Procedure in a Case with Prenatal Diagnosis of Congenital Microcystic Adenomatoid Malformation

Abstract: Massive microcystic congenital cystic adenomatoid malformation (CCAM) and bronchial atresia are associated with a high perinatal mortality secondary to lung hypoplasia and cardiac dysfunction, and fetal intervention should be considered to improve prognosis. Therapeutic options include open fetal surgery with pulmonary resection, fetal sclerotherapy and fetoscopy. We present a case with a severely enlarged left lung without ultrasound signs of dilated airways compatible with the diagnosis of microcystic CCAM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…However, it has been demonstrated that in experienced hands, fetal tracheoscopy for the treatment of fetuses with congenital diaphragmatic hernia can be achieved in a median surgical time of 10 min [15]. Similarly, we and others have demonstrated the feasibility of fetal airway endoscopy for cases with congenital high airway obstruction syndrome [16,17], bronchial atresia [18] and congenital microcystic adenomatoid malformation [19,20]. In this regard, it would be expected that fetal tracheoscopy in cases with neck masses may be more challenging due to severe distortion of the glottis, laryngeal and tracheal anatomy.…”
Section: Discussionmentioning
confidence: 86%
“…However, it has been demonstrated that in experienced hands, fetal tracheoscopy for the treatment of fetuses with congenital diaphragmatic hernia can be achieved in a median surgical time of 10 min [15]. Similarly, we and others have demonstrated the feasibility of fetal airway endoscopy for cases with congenital high airway obstruction syndrome [16,17], bronchial atresia [18] and congenital microcystic adenomatoid malformation [19,20]. In this regard, it would be expected that fetal tracheoscopy in cases with neck masses may be more challenging due to severe distortion of the glottis, laryngeal and tracheal anatomy.…”
Section: Discussionmentioning
confidence: 86%
“…In cases of non-hydropic fetuses with CPAM the prognosis is excellent with high survival rates and low postnatal morbidity, whereas fetuses with hydrops managed expectantly usually die either before or after delivery [ 2 , 3 , 35 ]. Therefore numerous attempts of fetal therapy have been made such as thoraco-amniotic shunting or thoracocentesis [ 5 , 22 , 36 ], prenatal open surgery with hysterotomy and lobectomy [ 3 , 6 , 37 ] and ultrasound-guided laser ablation [ 22 , 38 , 39 ], recently described by fetal bronchoscopy[ 40 ], or percutaneous radiofrequency [ 2 ]. Finally the treatment of fetuses with maternal steriod application is described in small retrospective trials and seems to be effective in microcystic lesions in presence of hydrops, where survival rates with expectant management are described as very low [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the collective evidence from previously published fetal tracheobronchoscopy cases 6 9 24 25 and ours adds to the current understanding of prenatal diagnosis and management of congenital lung lesions. Under the proper circumstances, fetal tracheobronchoscopy can serve as a diagnostic tool, as well as a possible therapeutic measure if an obstructive lesion is identified.…”
Section: Discussionmentioning
confidence: 56%
“…If an obstruction, such as bronchial atresia is encountered in utero, laser energy can be used to perforate the obstruction and re-establish luminal patency. 6 24 This not only allows the stored pulmonary mucus secretions to be expelled, but also normalization of the fetal lung tissue, correction of the mediastinal shift, and resolution of the hydrops fetalis. 6 24 …”
Section: Discussionmentioning
confidence: 99%